Exchange fluxes of NO2 and O3 at soil and leaf surfaces in an Amazonian rain forest - Gut, Andreas; Scheibe, Monika; Rottenberger, Stefanie; Rummel, Udo; Welling, M.; Ammann, Christoph; Kirkman, G. A.; Kühn, Uwe; Meixner, Franz X.; Kesselmeier, Jürgen; Lehmann, Bernhard E.; Schmidt, Wolfgang; et al. (Journal of Geophysical Research D: Atmospheres, 2002)
Trace gas exchange of NO2 and O3 at the soil surface of the primary rain forest in Reserva Biológica Jarú (Rondônia, Brazil) was investigated by chamber and gradient methods. The ground resistance to NO2 and O3 deposition to soil was quantified for dry and wet surface conditions using dynamic chambers and was found to be fairly constant at 340 ±110 and 190 ±70 s m-1, respectively. For clear-sky conditions, the thermal stratification of the air in the first meter from the forest floor was stable during daytime and unstable during nighttime. The aerodynamic resistance to NO2 and O3 deposition to the ground in the first meter above the forest floor was determined by measurements of 220Rn and CO2 concentration gradients and CO2 surface fluxes. The aerodynamic resistance of the 1-m layer above the ground was 1700 s m-1 during daytime and 600 s m-1 during nighttime. The deposition flux of O3 and NO2 was quantified for clear-sky conditions from the measured concentrations and the quantified resistances. For both trace gases, deposition to the soil was generally observed. The O3 deposition flux to the soil was only significantly different from zero during daytime. The maximum of- 1.2 nmol m-2 s-1 was observed at about 1800 and the mean daytime flux was -0.5 nmol m-2 s-1. The mean NO2 deposition flux during daytime was -1.6 ng N m-2 s-1 and during nighttime -2.2 ng N m-2 s-1. The NOx budget at the soil surface yielded net emission day and night. The NO2 deposition flux was 74% of the soil NO emission flux during nighttime and 34% during daytime. The plant uptake of NO2 and O3 by the leaves of Laetia corymbulosa and Pouteria glomerata, two typical plant species for the Amazon rain forest, was investigated in a greenhouse in Oldenburg (Germany) using branch cuvettes. The uptake of O3 was found to be completely under stomatal control. The uptake of NO2 was also controlled by the stomatal resistance but an additional mesophyll resistance of the same order of magnitude as the stomatal resistance was necessary to explain the observed uptake rate. Copyright 2002 by the American Geophysical Union.